2012
DOI: 10.2111/rem-d-11-00069.1
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Measurement of Leaf Area Index in Sagebrush-Steppe Rangelands

Abstract: Leaf area index (LAI) is defined as the one-sided area of leaves above a unit area of ground. It is a fundamental ecosystem parameter that is a required input of process-based plant growth and biogeochemical models. Direct measurement of LAI is the most accurate method, but is destructive, time-consuming, and labor-intensive. LAI is highly variable in time and space on sagebrush-steppe rangelands, and a rapid, nondestructive method is desirable to understand ecosystem processes. The pointintercept method is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…NS > 0·73, Table I) suggested that R-RHESSys can reasonably capture the variation of daily streamflow and baseflow for the Cleve Creek. The point-intercept-measured LAI for sagebrush-steppe ecosystems in the western USA averaged 0·33 m 2 m À2 (Finzel et al, 2012). Simulated annual mean LAI in the shrub-dominated watershed (Figure 1b) averaged 0·27 m 2 m À2 and ranged from 0·19 to 0·37 m 2 m À2 during 1991-2012, closing to reported data for similar ecosystems.…”
Section: Vegetation and Weather Forcing Datamentioning
confidence: 57%
See 2 more Smart Citations
“…NS > 0·73, Table I) suggested that R-RHESSys can reasonably capture the variation of daily streamflow and baseflow for the Cleve Creek. The point-intercept-measured LAI for sagebrush-steppe ecosystems in the western USA averaged 0·33 m 2 m À2 (Finzel et al, 2012). Simulated annual mean LAI in the shrub-dominated watershed (Figure 1b) averaged 0·27 m 2 m À2 and ranged from 0·19 to 0·37 m 2 m À2 during 1991-2012, closing to reported data for similar ecosystems.…”
Section: Vegetation and Weather Forcing Datamentioning
confidence: 57%
“…In addition, given that there is a lack of observed vegetation data, we compared the ranges of simulated leaf area index (LAI) and net primary productivity (NPP) of vegetation with previously published data for similar vegetation types (Gibbens et al, 1996;White et al, 2000;Tian et al, 2010;Finzel et al, 2012). These periods were selected because of the consistency of both weather records and observed daily streamflow data from the US Geological Survey gauge station.…”
Section: Modelling Protocol Model's Calibration and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ceptometer, measurement of LAI is an easy, quick and non-destructive method which has been used to observe various agronomic (switch grass, sagebrush-steppe, rangelands, maize, giant reed etc.) physiology and vegetative growth (Finzel et al 2012, Francone et al 2014. Nevertheless, this instrument has not been used in horticultural crops such as tomato and cucumber.…”
mentioning
confidence: 99%
“…Therefore, "indirect" non-contact measurements have been developed and are typically preferred. These techniques include a multitude of non-contact leaf area index (LAI) measurement tools, such as hemispherical photography, the Hemi-view Plant Canopy Analyser [3] from Delta-T Devices, the LAI-2000 Plant Canopy Analyser [4] from LI-COR Biosciences, the LP-80 AccuPAR ceptometer [5] from Decagon Devices, a mobile sensor combined with the canopy light transmittance model [6], the prototype sun-fleck LAI instrument named Tracing Radiation and Architecture of Canopies TRAC [7] and a Moderate Resolution Imaging Spectra-radiometer [8]. In addition, light detection and ranging technology (LiDAR), which has been applied to airborne [9] and terrestrial instruments [10], has been used to assess canopy structure and estimate vegetation attributes [11].…”
Section: Introductionmentioning
confidence: 99%